Pelaksanaan Pembelajaran Daring pada Mata Pelajaran PJOK SMP Negeri di Kecamatan Boja - Baskara, Ibrahim; Sudarmono, Martin (Indonesian Journal for Physical Education and Sport, 2023)
The Covid-19 phenomenon forces PJOK learning activities to be carried out online. This study aims to find out how the implementation of PJOK learning during the COVID-19 pandemic at State Junior High Schools throughout the Boja District, Kendal Regency. This study uses a qualitative method. Data collection techniques through observation, interviews, and documentation. The object of the research is a public junior high school in the District of Boja. The subjects in this study were principals, PJOK teachers, and students at state junior high schools throughout Boja District. The results showed that learning plans such as syllabus and lesson plans were sourced from the MGMP, while the implementation of learning was not in accordance with the existing lesson plans or could be said to adjust to the situation. The learning method used is the online method. The learning media used are Google Classroom, Zoom, Whatsapp and Goggle Drive. From the results of the study it can be concluded that in the aspect of learning planning it has been implemented quite well or not optimally. In the aspect of learning implementation, teachers have not used current technology, such as zoom or google classroom. In the evaluation aspect, all aspects of the assessment have been carried out. One of the obstacles in PJOK learning activities is unstable signal, limited quota and network, and there are some students who do not have mobile phones.